2019
DOI: 10.1002/mds.27712
|View full text |Cite
|
Sign up to set email alerts
|

Structural connectivity‐based topography of the human globus pallidus: Implications for therapeutic targeting in movement disorders

Abstract: Background Understanding the topographical organization of the cortico‐basal ganglia circuitry is of pivotal importance because of the spreading of techniques such as DBS and, more recently, MR‐guided focused ultrasound for the treatment of movement disorders. A growing body of evidence has described both direct cortico‐ and dento‐pallidal connections, although the topographical organization in vivo of these pathways in the human brain has never been reported. Objective To investigate the topographical organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 83 publications
(159 reference statements)
3
50
0
Order By: Relevance
“…More recently, Cacciola et al (2017b) provided a quantitative connectomic analysis revealing that the pallidal network mainly involves the sensorimotor areas (i.e., precentral and postcentral gyri), the superior frontal and paracentral gyri, with less representative widespread connectivity patterns with other important cortical areas (Cacciola et al, 2017b). These findings have been further corroborated by other diffusion tractography studies (da Silva et al, 2017; Grewal et al, 2018; Middlebrooks et al, 2018; Cacciola et al, 2019).…”
Section: Beyond the Direct Indirect And Hyperdirect Pathwayssupporting
confidence: 75%
See 1 more Smart Citation
“…More recently, Cacciola et al (2017b) provided a quantitative connectomic analysis revealing that the pallidal network mainly involves the sensorimotor areas (i.e., precentral and postcentral gyri), the superior frontal and paracentral gyri, with less representative widespread connectivity patterns with other important cortical areas (Cacciola et al, 2017b). These findings have been further corroborated by other diffusion tractography studies (da Silva et al, 2017; Grewal et al, 2018; Middlebrooks et al, 2018; Cacciola et al, 2019).…”
Section: Beyond the Direct Indirect And Hyperdirect Pathwayssupporting
confidence: 75%
“…Recently, Cacciola et al (2019) by using whole-brain tractography-based segmentation unveiled that the basal ganglia system is topographically organized in functionally segregated and integrated circuits within the GPi and GPe. In particular, the topographical organization of the cortico-pallidal pathway within the GP resulted in an antero-dorsal associative region and a posterior sensorimotor region, despite it was not possible to identify a well-defined limbic territory, thus suggesting that the cortico-pallidal fibers may provide only a relative contribution to the limbic territories in the GP.…”
Section: Beyond the Direct Indirect And Hyperdirect Pathwaysmentioning
confidence: 99%
“…On the other hand, diffusion-weighted imaging (DWI) and tractography represent powerful tools to trace structural connections non-invasively and in vivo (Cacciola et al 2016, 2017a, c, d, 2018, 2019; Milardi et al 2016a, b, 2017; Arrigo et al 2018; Calamuneri et al 2018), by estimating diffusion properties of magnetically labeled water molecules along myelinated axons (Basser et al 1994; Henderson 2012). Several tractography studies explored the structural connectivity of PAG in humans (Sillery et al 2005; Hadjipavlou et al 2006; Owen et al 2007, 2008; Ezra et al 2015), though only a few characterized either direct or indirect pathways between the PAG and cerebellum (Sillery et al 2005; Hadjipavlou et al 2006; Owen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Primates studies revealed that the main connectional systems of both pallidal segments are topographically organized, delineating limbic, associative and sensorimotor territories [ 3 , 4 , 5 ]. This peculiarity is shared across basal ganglia nuclei and it has been confirmed in human imaging studies carried out via diffusion magnetic resonance imaging (dMRI) and tractography-related techniques [ 6 , 7 , 8 , 9 ]. Such a topographical organization has gained increasing attention in behavioral neuroscience, as the tripartite organization matches existing evidence for motivational, cognitive and motor roles of the GP [ 10 ], as well as in functional neurosurgery for its therapeutic implications in movement disorders [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 85%